INNOVATION APPROACHES AND TECHNOLOGIES IN THE DEVELOPMENT OF REGIONAL ECONOMY: CURRENT RUSSIAN PRACTICE - Violetta V. Gassiy (Plekhanov Russian University of Economics, 2017)
Modernization of the system of state administration can allow us to coordinate and in due time fulfill proper functions. The article deals with modern technologies used in regional administration. Integration of these approaches and their upgrading could speed up the process of modernization of regional economy and its branches. The authors disclose the role of e-government and research different aspects of its impact on interconnected elements of regional economy, including those created by a common field for interaction of different target groups (bodies of state and municipal power, population, entrepreneurial structures).